Analisis Pengaruh Media Sosial terhadap Miant Beli Produk UMKM Kabupaten Purworejo di Yodotuku.com - Agus Fitri Yanto; Danis Imam Bachtiar; Astrianingsih Astrianingsih (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2023)
The rapid development of information and communication technology has changed the pattern of people's buying culture from offline to online. Finally, the product marketing strategy must also follow changes in the community, including the marketing of MSME products in Purworejo Regency. This research was conducted to find out more about the effect of social media promotion and electronic word of mouth (e-WoM) on buying interest of MSME products in Purworejo Regency at Yodotuku.com, either partially or simultaneously. The number of samples is 112 respondents selected by purposive sampling method. The instrument test uses validity and reliability tests. Data analysis technique using multiple linear regression.The results of the study show that social media promotion has a positive but not significant effect on the buying interest of MSME products in Purworejo Regency at Yodotuku.com. This is shown through the results of the t test of 0.329 (> 0.05). While e-WoM is known to have a significance value of 0.000 (<0.05), has a positive effect on consumer buying interest. Based on the test results, the calculated f is greater than the value of f table (64.353 > 3.08), it is known that simultaneously there is a positive and significant influence between social media promotion and e-WoM on the buying interest of UMKM Purworejo Regency products at Yodotuku.com. Therefore promotion on social media in the form of positive testimonials and reviews from consumers will be more optimal to influence buying interest for MSME products.